Manajemen Perencanaan Kepala Sekolah dalam Meningkatkan Produktivitas Kerja Guru di SMP Muhammadiyah 05 Medan - Kaban, Amelia Br; Tambusai, Nurul Hidayah; Radianti, Radianti; Mayshara, Viani Alya (Education Achievement: Journal of Science and Research, 2024)
This journal aims to analyze the role of school principala as motivator in improving teacher performance at SM Muhammadiyah 05 Medan. This research uses a qualitative approach with a case method. Data was collected through in-depth interviews with school principals, classroom observation, and analysis of related documents. Research shows that school principals play a key role in motivating teachers an improving their performance through various strategies and actions. The principal acts as a transformational leader who inspires teachers with aslear vision, provides support and constructive feedback, facilitating professional development, and creating a positive work environment. These findings undetline the important role of school principals in improving teacher performanceand povde sunggestions for future school leadership development.